EARTH2018 – International and Interdisciplinary Conference (diségno, 2019)
As one of the various events patronized by the Unione Italiana per il Disegno (UID), the International and Interdisciplinary Conference on Digital Environments for Education, Arts and Heritage (EARTH2018) was held on the 5th and 6th of July, 2018, at the Brixen campus of the Faculty of Education of the Free University of Bozen-Bolzano